Mathematics Practicum-Based Learning to Improve Critical Thinking Skills for Fourth Grade Students at Madrasah Ibtidaiyah - Anugrah, Muhamad; Mu'alim, Mu'alim (Thinking Skills and Creativity Journal, 2022)
The reality of education today is still limited to the transfer of knowledge, not to the transfer of value, which creates the concept of critical education, that education is a process in which a nation prepares its young generation to live and fulfill life goals effectively and efficiently. This study aims to analyze the effect of the Mathematics practicum-based learning method on critical thinking skills at Madrasah Ibtidaiyah. This type of research is causality research. The causality method is a study to determine whether there is a consequence of something that is imposed on the subject under investigation. The subjects in this study were fourth-grade students, totaling 32 students—data collection techniques using questionnaires and tests. Data analysis used Simple Regression analysis with the help of SPSS version 25. The results showed that the student responded positively to applying the Mathematics practicum-based learning method. It can be seen from 32 students who gave a positive response. The test results of students' critical thinking skills after showing students get a very good scores. It indicates that students' thinking ability is categorized as very high. The model's goodness shows the coefficient of determination (R-Square) of 0.437% or 43.7% of critical thinking variables explained by the variable using mathematics-based learning methods. Another variable explains the remaining 55.3%. It shows that applying practical learning methods is suitable in fourth-grade Madrasah Ibtidaiyah.